Authentic pedagogy: examining intellectual challenge in social studies classrooms. Issue 6 (2nd November 2018) - Saye, John W.; Stoddard, Jeremy; Gerwin, David M.; Libresco, Andrea S.; Maddox, Lamont E.
ABSTRACT: This paper reports results from a six-state study of 62 USA social studies classrooms. We examined the extent to which intellectually challenging authentic pedagogy was present in study classrooms, the characteristics of classroom practice at different levels of authentic pedagogy, and how those characteristics may promote or inhibit high levels of authentic intellectual work (AIW). Like earlier AIW studies, we found generally low levels of AIW in observed classes. However, we did find several cases of classrooms scoring in the highest AIW range. We examined characteristics of practice that typified teaching of exemplar lessons at four different levels of authentic pedagogy and identified noteworthy differences in teacher purpose, the ways teachers structured and enacted lessons to accomplish their purposes, and the ways that the structures of the lessons encouraged different lesson narratives that communicated different epistemological assumptions about the complexity of social reality and the process of sense-making. Teachers at the higher levels of the AIW scale sought to promote autonomy and civic competence. We conclude that to maintain democratic societies, educators must expand the number of classrooms offering students this essential preparation for civic life and provide suggestions for how this might be accomplished.